DIVERSITAS GASTROPODA (MOLUSKA) DARI SUNGAI BATANG KUMU PASIR PENGARAIAN KABUPATEN ROKAN HULU RIAU - Yolanda, Rofiza (Universitas Pasir Pengaraian, 2014)
Study about diversity of Gastropods (Mollusca) was conducted from April to August 2013 in Batang Kumu river, Pasir Pengaraian, Rokan Hulu Regency,Riau. The objective of the present study was to evaluate the diversity of Gastropods from the upper stream, middle stream and lower stream of the river by using 1 x 1 square transect. Total 181 individual/m2 of gastropods with 4 specieswere obtained, they are Pomacea canaliculata, Brotia sp., Melanoides tuberculata and Filopaludina javanica